W krzywym zwierciadle. O filmie „Superstar: The Karen Carpenter Story (1987)” Todda Haynesa - Karpińska, Zuzanna (Humaniora. Czasopismo Internetowe, 2025)
Only four years after Karen Carpenter’s death, Todd Haynes made an experimental “documentary” film about her life. However, Superstar: The Karen Carpenter Story is nothing like a classic biopic. Rather than employing a linear narrative structure based primarly on carefully selected archival material, the American director created a work that blends docudrama, horror, and rockumentary — with Barbie dolls playing the main characters. This paper analyses the 1987 film, focusing on the socio-cultural context in which it was created and the media environment from which the Carpenters’ music emerged. It explores why the director known for openly challenging the heteronormative vision of culture would choose to make a film on an artist often associated with that very vision. Drawing on studies of New Queer Cinema, Todd Haynes’s oeuvre, and media studies, the analysis suggests that Haynes’s use of postmodern art techniques reflects broader changes in U.S. society in the late 20th century. Social fragmentation, shifts in family structure, and the rise of television all shape the film and its themes. In other words, Haynes translates his views on recent reality into the so-called language of film. The framework of the film is set by the years of the Carpenters’ activity. At the same time, the director does not lose sight of the individuality of the main character of his film, Karen Carpenter, while going beyond the realm of film journalism, as Andrzej Pitrus points out.